(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study explored the potability of sachet water in Asaba, Southern Nigeria, using the Weighted Arithmetic Water Quality Index (WQIA) and Water Pollution Index (WPI). Using established parameters, the pH, turbidity, electrical conductivity, total dissolved solids (TDS), sulphate, phosphate, chloride, zinc, lead, and iron of 100 sachet water samples obtained from different retail locations in Asaba were analyzed. The results of the investigation were compared to the WHO and SON drinking water guidelines. The WQIA was used to categorize overall quality of sachet water, while the WPI provided details on the pollution status of each sample. The results showed that turbidity was between (0.00 - 0.62 NTU), pH (6.50 -7.60), electrical conductivity (24.60 -77.20 µS/cm), total dissolved solids (12.10 - 65.30 mg/L), sulphate (0.18 - 2.65 mg/L), phosphate (0.01 - 0.04 mg/L), chloride (3.10 - 39.30 mg/L), zinc (0.00 - 0.05 mg/L), lead (0.000 - 0.007 mg/L) and iron (0.02 - 0.09 mg/L. These results were all within the acceptable range for drinking water. The WQI value of 5.61 classified the sachet water as excellent, whilst the WPI value of 0.26 showed a very low pollution load. According to these results, the Asaba Metropolis’ sachet water is of excellent quality and safe for ingestion by humans. In order to uphold these high standards and guarantee ongoing public health protection, the article highlights the efficacy of present production techniques and regulatory processes while advising ongoing monitoring and quality verification.